Redefining health care : creating value-based competition on results - Porter, Michael E., 1947-; Teisberg, Elizabeth Olmsted (Boston, Mass. : Harvard Business School Press, 2006)
"Health care in the United States and other nations is on a collision course with patient needs and economic reality. Rising costs, mounting quality problems, and increasing numbers of citizens without health insurance are unacceptable--and unsustainable. In Redefining Health Care, Michael E. Porter and Elizabeth Olmstead Teisberg set forth a new vision of the health care system in which every actor is focused on improving value, as measured by health outcomes per dollar expended. The authors prescribe a powerful and actionable agenda for change"--P. [2] of cover.
Scoping the problem -- Identifying the root causes -- How reform went wrong -- Principles of value-based competition -- Strategic implications for health care providers -- Strategic implications for health plans -- Implications for suppliers, consumers, and employers -- Health care policy and value-based competition: implications for government.
Includes bibliographical references (pages [445]-488) and index.
Description based on print version record.
Keywords: Medical care -- Quality control; Medical care -- Cost control; Medical care -- Cost effectiveness; Value analysis (Cost control); Competition; Delivery of Health Care -- economics -- United States; Economic Competition -- United States; Health Care Costs -- United States; Quality of Health Care -- economics -- United States; Soins médicaux -- Qualité -- Contrôle; Soins médicaux -- Coût -- Contrôle; Soins médicaux -- Coût-efficacité; Analyse de la valeur; Compétitivité (Économie); Administração de serviços de saúde; Administração de serviços de saúde (controle de qualidade); Administração de serviços de saúde (custos); Competição econômica; Gesundheitswesen; Reform; Administração de serviços de saúde; Administração de serviços de saúde (controle de qualidade); Administração de serviços de saúde (custos); Competição econômica; Competition; Medical care -- Cost control; Medical care -- Cost effectiveness; Medical care -- Quality control; Value analysis (Cost control); POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; USA; elektronické knihy; electronic books